The repeated prisoner's dilemma in a network - Markus Kinateder (Fondazione Eni Enrico Mattei (FEEM), 2010)
Imperfect private monitoring in an infinitely repeated discounted Prisoner's Dilemma played on a communication network is studied. Players observe their direct neighbors' behavior only, but communicate strategically the repeated game's history throughout the network. The delay in receiving this information requires the players to be more patient to sustain the same level of cooperation as in a complete network, although a Folk Theorem obtains when the players are patient enough. All equilibria under exogenously imposed truth-telling extend to strategic communication, and additional ones arise due to richer communication. There are equilibria in which a player lies. The flow of information is related with network centrality measures.
Keywords: C72; C73; D85; 330; Repeated Game; Prisoner's Dilemma; Imperfect Private Monitoring; Network; Strategic Communication; Centrality